Technical advances in robot-assisted laparoscopic radical prostatectomy - Ryan Turpen; Hany Atalah; Li-Ming Su (Therapeutic Advances in Urology, 2009)
Since it was introduced in 1999, the da Vinci Surgical System has become an integral tool in urologic surgery, specifically in the management of localized prostate cancer. The original technique of robot-assisted laparoscopic prostatectomy (RALP) was developed and standardized in 2000 at the Institut Mutualiste Monsouris. Since that time, the technique of RALP has undergone various modifications. The driving force behind the evolution of the RALP technique in the past decade has been based on efforts to improve upon the three main objectives of surgery, namely the ‘trifecta’ of cancer cure and the preservation of potency and of urinary continence. In this review, we aim to provide an update on the midterm oncologic outcomes of RALP and focus specifically on two technical modifications that have been introduced in an effort to optimize the outcomes of potency and earlier return of urinary continence.